Technology to prevent Methane or coal dust explosions in the mine - Joldasbayeva Aysulu Baxitbay qizi; Ametov Ruslan Muxtar o’g’li; Embergenov Allabergen Polatbay o’g’li; Maulenov Nurlibek Axmet o’g’li; Kulmuratova Aliya Janabay qizi (Peerian Journals Publishing, 2022)
Preventing the propagation of methane or coal dust explosions through the use of active explosion-suppression systems remains one of the most underutilised explosion controls in underground coal mines. As part of the effort to develop better technologies to safeguard mines, the use of active barrier systems was investigated at Kloppersbos in South. From the tests conducted, it can be concluded that the ExploSpot System was successful in stopping flame propagation for both methane and methane and coal dust hybrid explosions when ammonium phosphate powder was used as the suppression material. The use of this barrier will provide coal mine management with an additional explosion control close to the point of ignition and may find application within longwall faces further protecting mines against the risk of an explosion propagating throughout a mine
Keywords: Coal; Methane; Explosions; Active barriers